ANALISIS AKUNTANSI PERSEDIAAN PRODUK RUSAK PADA TOKO ROSMART SUKARAJA KECAMATAN CURUP TIMUR - Upi Niarti (Jurnal Ilmiah Raflesia Akuntansi, 2021)
Abstrack-The problem of product damage is an important problem in the company. The bad influence that occurs in the company against this damaged product is in obtaining profits / profits.The purpose of this study was to analyze the causes of product damage, record and calculate the inventory of damaged products and analyze efforts to reduce damaged products at the Rosmart Sukaraja Store for five months, from January to May 2020. This research was clarified using descriptive quantitative research, to determine management of damaged or expired products at Rosmart Stores and inventory records for damaged products. From the results of this study indicate that at the Rosmart Store, for damaged products that cannot be returned to the distributor, the damaged product is discarded immediately, and recorded as the cost of the damaged product and automatically reduces the store's profit in selling the beverage product.